Syndrome of emotional burnout in the professional activity of the university teacher as a psychological and pedagogical problem - Romanovska, O. O. (Problems of Engineer-Pedagogical Education, 2018)
The problem of preserving the health of the university teacher is today one of the actual psychological and pedagogical problems of our time, since it is the teacher who owns one of the defining roles in ensuring the necessary high level of professionalism of future graduate specialists. The author notes that the professional activity of the teacher is one of the most stressful professions of our time and one of the most serious consequences of this is the syndrome of emotional or professional burnout. Also in the article it is noted that today in Ukraine the consequence of a very high intensity of work and nervous tension associated with the need to quickly introduce a significant amount of innovation in higher education institutions, the teachers began to form "emotional burnout syndrome." In the article the essence of the concepts of "burnout", "emotional burnout", "professional burnout of the university teacher" is considered. A study was carried out, which determined the importance of the problem of professional burnout and factors of its formation. The results of the study showed that today there are no comfortable conditions for maintaining the teacher's health in higher educational institutions, namely, there is no psychological and pedagogical support for the prevention of the emotional and mental state of university teachers.